Interplay of Economics, Entrepreneurship, and Auditing: Unveiling Financial Accountability and Performance in Business Ventures - Nugrahanti, Trinandari Prasetyo; Andriani , Eva; Majid, Jamaluddin; Syafri, Muhammad; Waoma, Samalua (West Science Journal Economic and Entrepreneurship, 2023)
This research delves into the complex interplay between economics, entrepreneurship, and auditing within the context of Micro, Small, and Medium-sized Enterprises (MSMEs) in West Java, Indonesia. The study focuses on uncovering the effects of these interactions on accountability mechanisms and financial performance. Employing a mixed-methods approach, the research integrates quantitative survey data with qualitative interview insights. The quantitative phase involves a structured survey to explore relationships, while the qualitative phase offers deeper insights from key stakeholders. The findings reveal the mediating role of accountability in the relationship between entrepreneurship and financial performance. Auditing practices emerge as strategic tools for promoting transparency and indirectly enhancing financial outcomes. Contextual factors, such as West Java's entrepreneurial ecosystem, contribute to shaping these interactions. The insights offer practical implications for policymakers, practitioners, and stakeholders to foster sustainable growth and accountability in the MSME sector.